Meningkatan Hasil Belajar IPA Materi Sifat-Sifat Benda Melalui Metode Eksperimen Pada Siswa Kelas III SDN 3 Bogangin - Aguntoro Aguntoro (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The aim is to improve student learning outcomes in science learning material properties of objects through the experimental method as a learning method for Class III SD Negeri 3 Bogangin, Sumpiuh District, Banyumas Regency. Research on improvement of learning with the experimental method as a learning method runs 2 cycles. The results showed that in the initial learning, the students who finished studying were 5 students from 12 children or 41.67 percent. In the first cycle of students who finished studying as many as 9 students from 12 students or as much as 75 percent. In the second cycle of students who finished studying as many as 11 students from 12 students or as much as 91.67 percent. Through the experimental method as a learning method in the science learning process the material properties of objects can improve students' understanding of the properties of solids, liquids and gases, create a more pleasant learning atmosphere and improve student learning outcomes for Class III SD Negeri 3 Bogangin.